Application of Fuzzy Logic Method and Analytical Hierarchy Process in Assessment of Education Quality at the Madrasah Aliyah Level - Andi, Muhammad Yusril Haffandi; Nurcahyo, Gunadi Widi; Hendrik, Billy (Universitas Putra Indonesia YPTK Padang, 2025)
Madrasas have a strategic role in producing a generation of the nation that is intellectually intelligent as well as spiritually and emotionally mature, but the quality between madrasas is still uneven, especially in rural areas such as Kerinci Regency. The assessment of the quality of madrasas until now tends to be subjective and has not been based on a measurable, systematic, and widely replicated system. This research aims to develop an objective and structured quality evaluation system for madrasah education using a technology-based approach. The methods used are Fuzzy Logic and Analytical Hierarchy Process (AHP) which are combined into Fuzzy AHP. The scope of the research is focused on aliyah madrasas under the coordination of the Ministry of Religious Affairs of Kerinci Regency. The data was obtained through direct interviews with the Head of the Madrasah Education Section and included eight aliyah madrasas as the object of the research, which were assessed based on nine main criteria: quality of teachers, teaching materials, infrastructure, school governance, learning environment, assessment system, leadership of school principals, parental support, and technology and digitalization. A web-based decision support system was developed to automatically manage Fuzzy AHP calculations, so that it can be used as a continuous evaluation tool. The results of the study show that this model is able to produce consistent, objective, and valid assessments with a Consistency Ratio (CR) value of < 0.1. Madrasah MA2 obtained the highest ranking in the assessment of the quality of education. The Fuzzy AHP approach has proven to be effective in multi-criteria education evaluation and can be the basis for policies that are more responsive to local needs.